Transformasi Sistem Pendidikan di Pesantren dalam Merespon Tuntutan Masyarakat Global - Rifah, Uli (AN NUR: Jurnal Studi Islam, 2023)
This article aims to discuss the transformation of the education system in pesantren in responding to the demands of the global community. In more detail, the formulation of the problems studied in this study is to discuss the transformation of pesantren education, global society, the purpose of transformation and the driving factors of the transformation of education in pesantren in responding to the demands of global society and responding to the demands of global society. This research uses a qualitative method. The data sources in the research are the ustaz and teachers, santri, santri guardians, employees and the surrounding community of Al Bukhori Islamic boarding school which is located in the village of Sengon, Tanjung sub-district, Brebes district. The data collection technique uses interviews, observation, documentation and literature study. The data analysis uses using data reduction method, triangulation method, display method and conclusion drawing method. This study concludes that the transformation that occurs in the Al Bukhori pesantren is one of the efforts to maintain its existence. The transformation process in the fields of education, institutional management, facilities and infrastructure and the economy began in 1971 and then continued subtly. Until this research was conducted at the end of the year two thousand and two recovered three the process was still ongoing. The most dominant factor influencing the transformation is the contextual needs of this Indonesian society affected by today's globalization, and the development of science and technology.